Community Empowerment On Sustainable Outdoor Recreation In Pangandaran Tourist Destination - Mega Fitriani Adiwarna Prawira; Aura Bulan Andhara Prawira; Eko Susanto (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This research examines the diverse forms of community involvement in tourism within Pangandaran Regency, highlighting its potential for sustainable development. The region features 270 tourist attractions categorized into cultural, man-made, and natural types, with a significant emphasis on eco- tourism and outdoor recreation opportunities, particularly in the Parigi sub-district. The growing number of restaurants and micro-enterprises reflects the evolving landscape of tourism-related economic activities and underscores the interconnection between the local and tourism industries. Active community participation in various tourism organizations indicates a robust network essential for promoting tourism activities and ensuring local stakeholders play a crucial role in the sector's growth and sustainability. Despite these strengths, the research identifies significant challenges related to infrastructure development, environmental sustainability, and community engagement. Overcrowding during peak seasons places pressure on local facilities, while a lack of awareness about sustainable tourism practices among residents hampers effective participation. Enhancing community education on eco-friendly practices and establishing collaborative frameworks among stakeholders is essential to cultivating a sustainable tourism ecosystem. By addressing these challenges and leveraging community strengths, Pangandaran can foster a tourism landscape that generates economic benefits while preserving its rich cultural and natural heritage. Promoting sustainable practices and fostering a sense of shared responsibility among residents will be crucial for ensuring the long-term viability and success of tourism in the region.